Use of the omentum majus in the therapy of postoperative sternal necrosis - Jakubaszko, Jacek; Domanasiewicz, Adam; Marczak, Jakub; Kustrzycki, Wojciech (Kardiochirurgia i Torakochirurgia Polska/Polish Journal of Thoracic and Cardiovascular Surgery, 2011)
Introduction : Deep sternal wound infection (DSWI) and sternal necrosis remain a dreaded complication of cardio-thoracic procedures. Among many available healing techniques none is the preferred one. Case report: We present a case of a 79-year-old female who underwent coronary artery bypass grafting with concomitant mitral repair in our unit. She went on to develop DSWI with sternal necrosis and mediastinitis during the postoperative course. After several attempts of surgical wound closure, we decided to implement an omental transfer with additional autologous skin grafting as an optimal technique for wound closure after the chest wall resection. After hospital day 65, the patient was discharged in a good general condition with local wound healing and satisfactory cosmetic effect.